Integrating LoRa SX178S with GPS Sensor for Free Geolocation - Satrio Yudho; Darma Rusjdi; Rizki Pratama Putra; Riki Ruli A. Siregar (Sekolah Tinggi Teknik - PLN, 2022)
Global positioning system known as an information which determine position of an object in standard value like Longitude and Altitude. due the trending development of Internet of things and its application, providing services is enable by using cellular networks which in metered connection. LoRa so-called long-range radio communication is one of wireless network sensor infrastructure that have an advantage in longer range operation. integrating LoRa with GPS module is one solution to provide location services with relatively free of cost. in this paper, we present our experiment of LoRa chipset SX76s and GPS module to aim the geolocation information to locate the device location.